2011
DOI: 10.1055/s-0030-1259956
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 2-Aryl-3-nitro-2H-chromenes Catalyzed by a Bifunctional Thiourea

Abstract: A bifunctional thiourea-catalyzed tandem approach of oxa-Michael-aza-Henry-desulfonamidation was used to synthesize chiral 2-aryl-3-nitro-2H-chromenes. This method provides direct access to the corresponding products in moderate to good yields and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Melting points are uncorrected and expressed in °C by MRS-2 Melting point apparatus from Shanghai Apparatus Co., Ltd. 1 H NMR and 13 C NMR spectra were measured in CDCl 3 , MeOD or DMSO-d 6 solution on a Bruker AV-400 or AV-500 spectrometer using TMS as an internal reference. Coupling constant (J) values are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting points are uncorrected and expressed in °C by MRS-2 Melting point apparatus from Shanghai Apparatus Co., Ltd. 1 H NMR and 13 C NMR spectra were measured in CDCl 3 , MeOD or DMSO-d 6 solution on a Bruker AV-400 or AV-500 spectrometer using TMS as an internal reference. Coupling constant (J) values are given in Hz.…”
Section: Methodsmentioning
confidence: 99%
“…Several reports describe construction of 2-aryl-3-nitro-2H-chromenes in good yields using 1,4-diazabicyclo[2.2.2]octane (DABCO), 7,8 L-pipecolinic acid 9 or C 2 -symmetric pyrrolidine-triazoles 10 as catalysts. The preparation of optically active 2-aryl-3-nitro-2H-chromenes through asymmetric tandem oxaMichael-Henry reactions has also been realized recently, with chiral pyrrolidine derivatives, 11,12 or cinchona alkaloid-derived bifunctional thioureas 13 as catalysts under mild conditions, respectively. Kinetic resolution of racemic 2-aryl-3-nitro-2H-chromenes can also be used to provide their enantioriched forms.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Schreiner et al [63] reported a bifunctional thiourea XXXIb catalyzed tandem reaction of salicyl- N -tosylimines 33 with nitroolefins 27 in toluene at room temperature for the synthesis of nitrochromenes 28 , which resulted in poor yield and good enantioselectivities. A broad range of substituted nitrostyrenes was studied for these tandem oxa -Michel-aza-Henry-desulfonamidation processes to afford the corresponding 2-aryl-3-nitro-2 H -chromenes by a kinetically controlled desulfonamidation step (Scheme 17).…”
Section: Reviewmentioning
confidence: 99%